How functional programming mattered - Hu, Zhenjiang; Hughes, John; Wang, Meng (National science review, 2015)
In 1989 when functional programming was still considered a niche topic, Hughes wrote a visionary paper arguing convincingly ‘why functional programming maters’. More than two decades have passed. Has functional programming really matered? Our answer is a resounding ‘Yes.’. Functional programming is now at the forefront of a new generation of programming technologies, and enjoying increasing popularity and inluence. In this paper, we review the impact of functional programming, focusing on how it has changed the way we may construct programs, the way we may verify programs, and fundamentally the way we may think about programs.